Complications of first tarsometatarsal joint arthrodesis - Masuda, Rodrigo Yuzo; Pereira, Vinicius Felipe; Lemos, Andre Vitor Kerber Cavalcante; Nery, Caio Augusto de Souza; Mansur, Nacime Salomão Barbachan (Journal of the Foot & Ankle, 2021)
Objective: First tarsometatarsal joint (TMTJ) arthrodesis, also known as Lapidus, is a surgical procedure used to treat severe hallux valgus, associated hypermobility of the first ray, and/or osteoarthritis of the first TMTJ. Despite the high satisfaction rate and high corrective power, this technique is not without complications. This study aimed to report the complications of first TMTJ arthrodesis. Methods: This is a case series of 16 patients treated with first TMTJ arthrodesis. Patients were evaluated based on foot radiographs, clinical alignment of the hallux, and signs and symptoms. Results: Eight patients had either major or minor complications. Three patients had recurrent deformity (1 with associated nonunion), 2 had delayed union, 2 had hardware loosening (1 with associated nonunion), and 1 had wound dehiscence. Conclusion: First TMTJ arthrodesis requires greater care in choosing the surgical technique for the treatment of hallux valgus. In addition, some points should be considered to minimize complications as much as possible. We believe that data are still scarce to provide a concrete basis. Level of Evidence IV; Therapeutic Studies; Case Series.